Are Angelman and Prader‐Willi syndromes more similar than we thought? Food‐related behavior problems in Angelman, Cornelia de Lange, Fragile X, Prader‐Willi and 1p36 deletion syndromes. (March 2015) - Welham, Alice; Lau, Johnny; Moss, Joanna; Cullen, Jenny; Higgs, Suzanne; Warren, Gemma; Wilde, Lucy; Marr, Abby; Cook, Faye; Oliver, Chris
<x xml:space="preserve">Abstract</x> Food‐related behavior problems are well documented in Prader–Willi syndrome (PWS), with impaired satiety, preoccupation with food and negative food‐related behaviors (such as taking and storing food) frequently reported as part of the behavioral phenotype of older children and adults. Food‐related behavior problems in other genetic neurodevelopmental syndromes remain less well studied, including those seen in Angelman Syndrome (AS), the 'sister imprinted disorder' of PWS. Food‐related behavior problems were assessed in 152 participants each with one of five genetic neurodevelopmental syndromes – PWS, AS, 1p36 deletion, Cornelia de Lange, and fragile X. Predictably, levels of food‐related behavior problems reported in participants with PWS significantly exceeded those of at least one other groups in most areas (impaired satiety; preoccupation with food; taking and storing food; composite negative behavior). However, in some areas people with AS were reported to display food‐related problems at least as severe as those with PWS, with the AS group reported to display significantly more food‐related behavior problems than at least one comparison group on measures of taking and storing food, composite negative behaviors, impaired satiety and preoccupation with food. Over 50% of participants in the AS group scored above the median point of the distribution of PWS scores on a measure of taking and storing food. These findings indicate further investigation of eating problems in AS are warranted and have implications for current theoretical interpretations of the behavioral differences between AS and PWS. © 2015 Wiley Periodicals, Inc.